THE INFLUENCE OF BREEDER KNOWLEDGE IN THE UTILIZATION OF AGRICULTURAL WASTE AS BEEF CATTLE FEED IN SAMANGKI VILLAGE,SIMBANG DISTRICT,MAROS REGANCY - FAHARUDDIN, ANDI FITRI; Abdullah, Agustina (Agrisaintifika: Jurnal Ilmu-ilmu Pertanian, 2023)
AbstractThe purpose of this study was to determine whether factors Cosmopolitan , Education and Extension Intensity significant effect either simultaneously or partially on Knowledge Breeders In Agricultural Waste Utilization For Beef Cattle Feed Samangki Village , District Simbang , Maros. Partially research results obtained Cosmopolitan factor ( X1 ) and counseling intensity (X2) significantly affects Breeders Knowledge in Agricultural Waste Utilization For Beef Cattle Feed ( Y ) , while counseling intensity ( X2 ) no significant effect on the Breeders Knowledge Utilization of Agricultural Wastes For Beef Cattle Feed ( Y ) . Simultaneously Cosmopolitan factor ( X1 ) and counseling intensity ( X2 ) significantly influence Breeders Knowledge in Agricultural Waste Utilization For Beef Cattle Feed ( Y ) .Keywords :  Breeders Knowledge , Cosmopolitan , Counseling Intensity